EFFECT OF TAT, IT, FAT AND WCT ON ROA ON THE CONSUMER GOODS INDUSTRY SECTOR - Jessy Safitri Sitorus; Cindy Devona E Sitohang; Kartika Hardjunan; Raja Nai Zebua (Jurnal Ipteks Terapan (Research Of Applied Science And Education ), 2021)
This study was conducted to identify how much influence Total Assets Turnover, Inventory Turnover, Fixed Assets Turnover and Working Capital Turnover have on Return On Assets in consumer goods industry companies for the 2017-2019 period. The population of this research amounted to 54 companies "which are listed on the Indonesia Stock Exchange." As for the "sample" used was determined by the purposive sampling method," it was found that a sample of 45 companies multiplied by 3 years was 135 samples. The data analysis method used is descriptive statistical analysis and multiple linear regression analysis. The results of this research simultaneously show that Total Assets Turnover, Inventory Turnover, Fixed Assets Turnover and Working Capital Turnover have a significant and significant effect on Return On Assets. Partially, Total Assets Turnover, Fixed Assets Turnover and Working Capital Turnover have no and no significant effect on Return On Assets. While Inventory Turnover partially and significantly affects Return On Assets